Spatial languages in IsiXhosa - Botsis, Rachel (Linguistics, 2017)
This thesis investigates some aspects of spatial language of isiXhosa. It identifies the elements of isiXhosa used in the spatial domain and analyses their use and distribution across the language. Six isiXhosa-speaking language consultants were interviewed, all males between the ages of eighteen and twenty-two years. They have all grown up in the Eastern Cape province of South Africa and are currently attending tertiary institutions within the Western Cape. The methodological framework adopted for this research was developed by the 'Max Planck Institute for Psycholinguistics' (MPI) in Nijmegen, Netherlands. Their research tools "Man & Tree" and "Space Games" were employed to gather the language data on spatial language of isiXhosa. A particular focus in this study was placed on investigating the underlying spatial models employed in the deictic axis, i.e. the face to face model or the single file model. The data reveals that both models seem to be employed by the young male isiXhosa-speakers of the study. Furthermore, the thesis also analyses what frames of reference these particular isiXhosa speakers utilize. The survey revealed variation in the use of models among these young speakers. This variation can be explained as language contact phenomena since all language consultants are in an English speaking environment at least for several years.